2009
DOI: 10.1007/s11256-009-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Only the Names Have Been Changed: Ability Grouping Revisited

Abstract: In this paper,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…For example, in their study of secondary English instruction, Caughlan and Kelly () argued that track labels may reinforce and activate the cultural models (Holland, Skinner, Lachicotte, & Cain, ) that secondary school teachers hold of high‐ and low‐track students, which in turn can result in instruction that is less engaging and coherent for low‐track students. Likewise, interviews with 25 sixth‐grade teachers from one school district in Texas found similar results and showed that the teachers had lowered expectations, assigned less work in class and less homework, and adjusted their assignments to make the work less demanding for students in their non‐honors classes (Worthy, ).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For example, in their study of secondary English instruction, Caughlan and Kelly () argued that track labels may reinforce and activate the cultural models (Holland, Skinner, Lachicotte, & Cain, ) that secondary school teachers hold of high‐ and low‐track students, which in turn can result in instruction that is less engaging and coherent for low‐track students. Likewise, interviews with 25 sixth‐grade teachers from one school district in Texas found similar results and showed that the teachers had lowered expectations, assigned less work in class and less homework, and adjusted their assignments to make the work less demanding for students in their non‐honors classes (Worthy, ).…”
mentioning
confidence: 89%
“…Teachers of high‐track classes spend more time studying literature and working on analytical writing, whereas low‐track classes have more emphasis on grammar and narrative writing (Gamoran & Carbonaro, ; Oakes, ). Students in high‐track classes are given more uninterrupted, sustained time to read in class (Worthy, ). In addition, the instruction in low‐track classes is often more fragmented and less coherent than in high‐track classes (Caughlan & Kelly, ; Page, ), with students working on isolated, basic skills (Worthy, ).…”
Section: Tracking and Instruction In Elamentioning
confidence: 99%
“…Conversely, according to Worthy (2010), homogeneously grouped low-track classes are the most difficult to teach and hardest to manage (Worthy, 2010).…”
Section: Literaturementioning
confidence: 99%
“…Researchers have studied different styles of between-class ability grouping such as multilevel classes (Gentry & MacDougall, 2009;Kulik & Kulik, 1992;Tieso, 2003), cross-grade grouping (Kulik & Kulik, 1992;Tieso, 2003), school-wide cluster grouping (Brulles, Peters, & Saunders, 2012;Gentry & MacDougall, 2009;Matthews et al, 2009), total-school cluster grouping (Gentry & Owen, 1999;Gentry & MacDougall, 2009), and tracking (Gentry & MacDougall, 2009;Matthews et al, 2009;Worthy, 2010).…”
Section: Between-class Ability Groupingmentioning
confidence: 99%
“…Tracking refers to the permanent assignment of students to classrooms for instruction and is commonly seen at the secondary level (Gentry & MacDougall, 2009). Students placed in high-tracked classes experience a faster paced, more challenging workload, whereas students in low-tracked classrooms focus on basic literacy skills, test preparation, with low-level materials (Worthy, 2010). Tracking differs from flexible ability grouping because the sequence of courses for students at specific ability levels or tracks are considered full-time and are rarely adjusted (Matthews et al, 2013).…”
Section: E Trackingmentioning
confidence: 99%